Smart cities – smart mobility : the impact of multimodal mobility services in the metropolitan area of Lisbon - Bernardo, Mafalda Ramos (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management